The Effect Of Company Age, Capital Intensity And Audit Committee On Tax Avoidance - Ni Komang Nindya Anjani Ariella; Ni Ketut Rasmini (Jurnal Ekonomi, 2024)
Tax avoidance is one of the tax planning that is carried out legally and does not violate tax regulations for the purpose of minimizing the tax burden by taking advantage of weaknesses in tax provisions. The purpose of this study was to analyze and provide empirical evidence on the effect of company age, capital intensity, and audit committee on tax avoidance. The research population is mining sector companies listed on the Indonesia Stock Exchange for the period 2018-2022. The sample of this study was selected using a nonprobability sampling method with a purposive sampling technique so that 15 companies were selected and a total of 75 observations. This research data analysis technique uses multiple linear regression analysis. The results of this study indicate that company age and capital intensity have a positive effect on tax avoidance. The audit committee has no effect on tax avoidance. The results of this study confirm the theory of planned behavior which explains that the existence of beliefs about the existence of things that support behavior will encourage the intention to carry out this behavior.